Multiscale dynamical analysis of a high‐resolution numerical model simulation of the Solomon Sea circulation. Issue 9 (18th September 2014) - Djath, Bughsin'; Verron, Jacques; Melet, Angelique; Gourdeau, Lionel; Barnier, Bernard; Molines, Jean‐Marc
Abstract A high 1/36° resolution numerical model is used to study the ocean circulation in the Solomon Sea. An evaluation of the model with (the few) available observation shows that the 1/36° resolution model realistically simulates the Solomon Sea circulations. The model notably reproduces the high levels of mesoscale eddy activity observed in the Solomon Sea. With regard to previous simulations at 1/12° resolution, the average eddy kinetic energy levels are increased by up to ∼30–40% in the present 1/36° simulation, and the enhancement extends at depth. At the surface, the eddy kinetic energy level is maximum in March‐April‐May and is minimum in December‐January‐February. The high subsurface variability is related to the variability of the western boundary current (New Guinea Coastal Undercurrent). Moreover, the emergence of submesoscales is clearly apparent in the present simulations. A spectral analysis is conducted in order to evidence and characterize the modeled submesoscale dynamics and to provide a spectral view of scales interactions. The corresponding spectral slopes show a strong consistency with the Surface Quasi‐Geostrophic turbulence theory.